SUBSTITUTING CORN STEEP LIQUOR WITH UREA AS NITROGEN EQUIVALENCE ON NUTRIENTS INTAKE, DIGESTIBILITY, BLOOD BIOCHEMISTRY AND MILK COMPOSITION IN EARLY LACTATING NILI-RAVI BUFFALOES - M. S. Qamar; Mahr-Un-Nisa; M. Sarwar; Zia-Ul-Rahman; T. Huma (Journal of Animal and Plant Sciences, 2016)
This study was conducted to examine the influence of varying levels of corn steep liquor (CSL) on feed intake, nutrient digestibility, nitrogen balance, milk composition and blood biochemistry in early lactating nili-ravi buffaloes. Twenty five early lactating buffaloes were divided into five groups, 5 animals in each group, using Randomized Complete Block Design. The animals were divided into different blocks to account for the variation in their age, parity and physiological stage. Five isonitogenous (17% CP) and isocaloric (2.82 Mcal/kg) diets were formulated. The control diet (C) had 0% CSL and in CSL20, CSL40, CSL60 and CSL80 diets, 20, 40, 60 and 80% urea on nitrogen equivalent was replaced by CSL, respectively. Animals were fed twice daily at ad libitum. The daily feed offered and refusals were recorded to calculate dry matter intake (DMI). The sample of feed offered and refusal were used to determine dry matter (DM), crude protein (CP), neutral detergent fiber (NDF) and acid detergent fiber (ADF). The DM, CP, NDF and ADF intake by buffaloes fed all diets remained unchanged (P>0.05). The DM and NDF digestibility were higher (P<.05) in animals fed diets containing CSL than those fed C diet. However, CP and ADF digestibility remained unaltered (P>0.05) across all diets. Plasma urea nitrogen (PUN) was lowest in buffaloes fed CSL80, CSL60 and CSL40 diets and was highest in buffaloes fed C diet.  Nitrogen balance remained significant (P<0.05) higher in buffaloes fed CSL diets as compared to those fed C diet. However, there had been a non-significant difference in nitrogen balance in animals fed CSL20, CSL40 and CSL60 diets. Nitrogen intake, fecal nitrogen and urinary nitrogen values remained unchanged across all diets. The triiodothyronine (T3), thyroxine (T4) and their ratio remained unchanged (P>0.05) across all diets. Milk production, its fat, protein, true protein, non-protein nitrogen (NPN) and solid not fat values remained unaltered across all diets. The 4% fat corrected milk and lactose were higher (P<.05) in milk of buffaloes fed CSL40, CSL60 and CSL80 diets than those fed CSL20 and C diets. In conclusion, buffaloes fed diets containing CSL ate more DMI, had higher digestibility, better nitrogen balance, produced more milk and lower PUN than those fed C diet.`
Keywords: Corn Steep Liquor; Buffaloes; Blood Biochemistry; Milk production